KINDS OF TRANSLATION USED IN TRANSLATING BUDI DOREMI’S SONG ENTITLED “MELUKIS SENJA” TRANSLATED BY EMMA HEESTERS - Wati Purnama Sari (Asosiasi Dosen Muda Indonesia, 2022)
The aim of this research is to identify the kinds of translation used in translating Budi Doremi’s song entitled “Melukis Senja” translated by Emma Heesters. The method used in this research is a descriptive-qualitative method. In analyzing the data, the researcher used kinds of translation theory advocated by Larson. The research results indicated that there are 19 data found in the translation of Budi Doremi’s song entitled “Melukis Senja” translated by Emma Heesters. From 19 data, there are 3 kinds of translation used namely modified literal translation (7 data), idiomatic translation (2 data) and unduly free translation (10 data). The unduly free translation is mostly used in translating the song lyrics because the translator added information in the target language and changed the meaning of the source language to the target language in order to create specific reactions for the target language listeners.